Applying a hexapod circular frame to gradually correct persistent knee flexion due to congenital aplasia of the quadriceps—a case report and review of the literature - Pilloux, Maxime; Aye, Victor; Fasel, Dimitri; Paris, Elio; De Marco, Giacomo; Vazquez, Oscar; Steiger, Christina; Dayer, Romain; Boudabbous, Sana; Ceroni, Dimitri (Frontiers in Pediatrics, 2025)
Congenital aplasia or hypoplasia of the quadriceps muscle are rare conditions that significantly impair the extension of the knee joint, resulting in a sustained flexion deformity. These conditions alter overall gait quality, impede daily activities and require effective, timely intervention. Surgical techniques for correction have been described, including soft-tissue release, guided growth, tendon transfer and external fixators. Among the external fixators available, hexapod circular frames are probably the most effective because they enable the precise, progressive correction of complex multiaxial deformities. We present the case of a 10-year-old girl with quadriceps aplasia and a severe flexion contracture of the knee. Surgical treatment involved the mobilisation of the patella, a transfer of hamstring tendons and the application of a hexapod circular frame to control the correction of the flexion deformity. This case study provides a glimpse into the use of hexapod circular frames to remediate severe knee flexion deformities that were previously believed to be irreversible due to the patient's quadriceps muscle aplasia. Safe, controlled aplasia correction greatly improves children's gait and functional ability to move around, making it an invaluable technique for managing difficult congenital knee problems.